2021
DOI: 10.1504/ijbge.2021.113942
|View full text |Cite
|
Sign up to set email alerts
|

Internal corporate governance mechanisms and financial performance: evidence from the UK's top FTSE 100 listed companies

Abstract: This paper examines the relationship between internal corporate governance mechanisms and the financial performance of the UK's top FTSE 100 firms listed on the London Stock Exchange. By using a sample of 59 firms from the top FTSE 100 firms over the period from 2013 to 2018, our findings demonstrated that the lower number of board size and independent directors on the board, the better financial performance of the UK's top FTSE 100 listed firms. However, our study revealed that better financial performance is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 98 publications
1
1
0
Order By: Relevance
“…The data also indicate that the average (median) number of independent directors on the audit committee is 2.8 (3.0), ranging from 1 to 15. These statistics align with previous studies that have found a positive correlation between a higher proportion of independent directors and improved corporate transparency (e.g., Crespí‐Cladera & Pascual‐Fuster, 2014; Elmghaamez & Akintoye, 2021). Furthermore, the number of non‐executive directors on the audit committee ranges from 1 to 11, with an average of 3.0 and a standard deviation of 2.0, which adheres to the requirement of the UK code for at least three independent non‐executive directors.…”
Section: Empirical Analysissupporting
confidence: 90%
“…The data also indicate that the average (median) number of independent directors on the audit committee is 2.8 (3.0), ranging from 1 to 15. These statistics align with previous studies that have found a positive correlation between a higher proportion of independent directors and improved corporate transparency (e.g., Crespí‐Cladera & Pascual‐Fuster, 2014; Elmghaamez & Akintoye, 2021). Furthermore, the number of non‐executive directors on the audit committee ranges from 1 to 11, with an average of 3.0 and a standard deviation of 2.0, which adheres to the requirement of the UK code for at least three independent non‐executive directors.…”
Section: Empirical Analysissupporting
confidence: 90%
“…However, Table 8 reports that the governance disclosure (GDS) has an insignificant effect on the return on capital of both product and service-based firms listed on LSE. This result is consistent with the findings reported by Elmghaamez and Akintoye (2021) who argued that better governance performance depends not merely on governance disclosure but also on the board compensation. However, the neoclassical theory supports the findings of the insignificant negative impact of GDS on the return on capital of the product and service-based firms listed on LSE.…”
Section: Additional Analysissupporting
confidence: 93%
“…This study also argues that there has been an increase Corporate governance structure plays an essential role in disciplining management and determining firm performance, especially in stock markets with effective corporate control (Elmghaamez & Ntim, 2016). Therefore, the board's characteristics significantly affect the shareholder's control (Hu & Izumida, 2008;Elmghaamez & Akintoye, 2021). Furthermore, several researchers found a dynamic relationship between corporate governance and corporate performance (e.g., Raheja, 2005;Harris & Raviv, 1988).…”
Section: Introductionmentioning
confidence: 77%